2013
DOI: 10.2139/ssrn.2465902
|View full text |Cite
|
Sign up to set email alerts
|

Gender Quotas and the Crisis of the Mediocre Man: Theory and Evidence from Sweden

Abstract: We develop a model where party leaders choose the competence of politicians on the ballot to trade o¤ electoral success against their own survival. The predicted correlation between the competence of party leaders and followers is strongly supported in Swedish data. We use a novel approach, based on register data for the earnings of the whole population, to measure the competence of all politicians in seven parties, 290 municipalities, and ten elections . We ask how competence was a¤ected by a "zipper" quota, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Indeed, despite the concern that these policies bring undeserving or unambitious female candidates into political office, empirical studies typically indicate that quota women are as (or even more) qualified as their male counterparts. In Sweden, Besley et al (2013) find that party-based gender quotas have a positive effect on men's competence, mainly due to the replacement of mediocre male leaders with more competent men. Other studies have found a positive link between (both male and female) politicians' education levels and quota implementation (Baltrunaite et al 2014;Casas-Arce and Saiz 2011).…”
Section: Acceleration Effects: Quotas Facilitating Women's Access To mentioning
confidence: 94%
“…Indeed, despite the concern that these policies bring undeserving or unambitious female candidates into political office, empirical studies typically indicate that quota women are as (or even more) qualified as their male counterparts. In Sweden, Besley et al (2013) find that party-based gender quotas have a positive effect on men's competence, mainly due to the replacement of mediocre male leaders with more competent men. Other studies have found a positive link between (both male and female) politicians' education levels and quota implementation (Baltrunaite et al 2014;Casas-Arce and Saiz 2011).…”
Section: Acceleration Effects: Quotas Facilitating Women's Access To mentioning
confidence: 94%
“…We cannot automatically infer that men are present in these proportions because they were the best representatives available. Baltrunaite et al (2012) find that feminizing legislatures through quotas leads to an increase in the quality of both male and female politicians, a finding supported by Besley et al (2012) and Júlio and Tavares (2010), suggesting that the composition of legislatures pre-quotas was sub-optimal.…”
mentioning
confidence: 89%
“…Yet, many empirical studies of candidate quality still focus on income and education rather than the character traits driving candidate selection (Baltrunaite et al 2012;Besley et al 2012;Galasso and Nannicini 2011;Júlio and Tavares 2010;Kotakorpi and Poutvara 2010).…”
Section: Rethinking the Criteria For Being A Good Representativementioning
confidence: 99%
See 1 more Smart Citation
“…That is, instead of using candidates' level of education we focus on candidates' job (Besley et al, 2017). We estimated each candidate's salary based on the average national salary of her profession, which we used to compute coalitions' average salary.…”
Section: Alternative Dependent Variablesmentioning
confidence: 99%